Study of the Nature and Location of Silver in Ag-Exchanged Mordenite Catalysts. Characterization by Spectroscopic Techniques - Aspromonte, Soledad Guadalupe (2013)
Catalysts based on Na-mordenite (symbolized as M) exchanged with 5, 10, and 15 wt % of Ag were characterized by X-ray photoelectron spectroscopy (XPS), extended X-ray absorption fine line structure (EXAFS), X-ray absorption near edge spectroscopy (XANES) and UV-vis diffuse reflectance spectroscopy (DRS) to investigate the effect of different treatments on the chemical state and surface concentration of the silver species. The AgxM catalysts were analyzed in oxidizing (O2) or reducing (H2/Ar) atmospheres and also after being used in the selective catalytic reduction of NOx or in successive cycles of toluene adsorption/desorption. In calcined samples, EXAFS profiles showed two types of AgO spheres of coordination, one due to a dispersed phase of silver oxide and the other due to Ag+ ions in interaction with the oxygen of the zeolite framework. The UV-vis DRS spectra showed the coexistence of isolated Ag+, Agn(delta)+ (n < 10) cationic clusters and AgxO particles. In addition, through the modified Auger parameter (alpha), calculated from XPS measurements, it was possible to identify Ag+ ions at exchange sites (alpha = 722 eV) and AgxO ( alpha = 725 eV) highly dispersed on the surface. Both species constitute stable active centers for the selective catalytic reduction of NOx under severe reaction conditions. However, during the adsorption-desorption of toluene, the reduction of silver oxides produces Ag(0) due to thermal hydrocarbon decomposition.